2023
DOI: 10.1172/jci.insight.164608
|View full text |Cite
|
Sign up to set email alerts
|

ABT1 modifies SMARD1 pathology via interactions with IGHMBP2 and stimulation of ATPase and helicase activity

Abstract: 1. Ownership: CLL is co-founder and chief scientific officer of Shift Pharmaceuticals. 2. Income: CLL has received in excess of $10,000 in income per annum from Shift Pharmaceuticals. 3. Research support. Research in the CLL and MAL labs have been supported by subawards from Shift Pharmaceuticals (as part of grants from the DOD, CMT Research Foundation and the NIH). 4. Intellectual property. CLL and MU share patents on novel compounds licensed by Shift Pharmaceuticals and planned patents for additional novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Preserving epigenetic markings is especially significant in the IGHMBP2 disease spectrum, where there is currently limited evidence of a correlation between genotype and phenotype, whereby patients with the same mutations may present vastly different disease courses [ 10 , 15 ]. So far, only one gene, ABT1 has been confirmed as an IGHMBP2 disease-modifying gene in humans [ 17 ]. As other disease modifier genes or epigenetic markers for IGHMBP2 disorders are currently unknown [ 2 , 9 , 17 ], modeling tools that preserve as many epigenetic markings as possible are essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preserving epigenetic markings is especially significant in the IGHMBP2 disease spectrum, where there is currently limited evidence of a correlation between genotype and phenotype, whereby patients with the same mutations may present vastly different disease courses [ 10 , 15 ]. So far, only one gene, ABT1 has been confirmed as an IGHMBP2 disease-modifying gene in humans [ 17 ]. As other disease modifier genes or epigenetic markers for IGHMBP2 disorders are currently unknown [ 2 , 9 , 17 ], modeling tools that preserve as many epigenetic markings as possible are essential.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently little evidence of a genotype–phenotype correlation, as patients with the same mutations in IGHMBP2 may present vastly different disease courses, including variable time of onset, phenotype and progression [ 14 , 15 ]. Though several other modifiers have been reported in mouse models [ 16 ], so far, ABT1 is the only confirmed disease modifier found in humans [ 17 ]. For IGHMBP2 restoration, we have previously developed a promising AAV9-based gene therapy, which is currently in Phase I/IIa clinical trials for IGHMBP2-related disorders (NCT05152823) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An association between ABT1 and IGHMBP2 was shown by co-immunoprecipitation when FLAG-IGHMBP2 and myc-ABT1 were co-transfected into HEK 293T cells [31,34]. Another study by Vadal and colleagues showed that the direct, high-affinity binding of ABT1 to IGHMBP2 increased ATPase and helicase activity and the processivity of IGHMBP2 [32].…”
Section: Modifiers Of Ighmbp2 Deficiencymentioning
confidence: 98%
“…IGHMBP2 also interacts with Reptin and Pontin, both of which play roles in U3 snoRNP biogenesis by interacting with U3 snoRNA [31]. The binding of IGHMBP2 to the activator of basal transcription (ABT1) in a complex by binding to the 5 ′ external transcribed spacer and the U3 snoRNA is important for pre-rRNA processing [32] (Figure 2A,B).…”
Section: Ighmbp2 Function and Modifiers Of Ighmbp2 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation